Focal Eosinophilic Myositis Affecting the Orbicularis Muscle: Clinical and Image Aspects - Galindo-Ferreiro, Alicia; Nieto, Maria Angeles Torres; Ajo, Julia Barbado; Schellini, Silvana [UNESP] (Wolters Kluwer, 2020)
Focal eosinophilic myositis (FEM) is a rare disease that is even more uncommon in affecting the periocular area. The authors are reporting the first case of FEM occurring in the lower eyelid of a 45-year-old Caucasian female who presented with localized painful area of glossy induration and peau d'orange skin lesion. Magnetic resonance image shows significant hyperintense thickening of the pre-septal orbicularis muscle region on T2-weighted images. Incisional biopsy of the induration revealed marked fibrinoid degeneration of the orbicularis muscle and adjacent fascia, mixed cellular infiltration of lymphocytes and eosinophils and a predominant CD8+ lymphocytic infiltrates in the immunohistochemical study. The final diagnosis was FEM.